2021
DOI: 10.3389/fphar.2021.698352
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Auraptene as an Anticancer Agent

Abstract: Auraptene is a bioactive monoterpene coumarin isolated from Citrus aurantium and Aegle marmelos that belong to the Rutaceae family. Auraptene can modulate intracellular signaling pathways that control cell growth, inflammation and apoptosis and can exert pharmacological properties such as anti-bacterial, anti-fungal, antileishmania and anti-oxidant activity. Auraptene had inhibitory and chemo-preventive effects on the proliferation, tumorigenesis and growth of several cancer cell lines through increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Coumarins are a well-known family of naturally occurring molecules with a diverse range of pharmacological and biological activities owing to the privileged structure and physicochemical properties of the 2-benzopyrone moiety (Figure ). , Indeed, many natural and synthetic coumarins exhibit antibacterial, antiviral, antioxidant, anticoagulant, and antitumor activities, among others, and are also used in the industry as food additives and as cosmetics and perfume ingredients. , The anticancer properties of the coumarin pharmacophore have been widely investigated, and current research efforts are dedicated to the design and development of novel coumarin analogues with the aim of addressing toxic side effects and inherent or acquired resistance of chemotherapeutic drugs in clinical use. …”
Section: Introductionmentioning
confidence: 99%
“…Coumarins are a well-known family of naturally occurring molecules with a diverse range of pharmacological and biological activities owing to the privileged structure and physicochemical properties of the 2-benzopyrone moiety (Figure ). , Indeed, many natural and synthetic coumarins exhibit antibacterial, antiviral, antioxidant, anticoagulant, and antitumor activities, among others, and are also used in the industry as food additives and as cosmetics and perfume ingredients. , The anticancer properties of the coumarin pharmacophore have been widely investigated, and current research efforts are dedicated to the design and development of novel coumarin analogues with the aim of addressing toxic side effects and inherent or acquired resistance of chemotherapeutic drugs in clinical use. …”
Section: Introductionmentioning
confidence: 99%
“…Of the studied compounds, auraptene is promising for further studies. This compounds exerted chemopreventive and antiproliferative effects on several cell lines via targeting different cell signalling pathways, and it has also an excellent safety profile based on animal studies ( Tayarani-Najaran et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coumarins such as AUR have anticancer properties at low concentrations and are suitable candidates to be utilized as adjuvants for radiotherapy as well as to minimize IR-induced adverse effects. [7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Auraptene (AUR), also known as 7-geranyloxycoumarin, is a coumarin with the ability to exert anticancer effects by interfering with various signaling pathways related to cytokines, growth factors, or apoptosis (Fig. 1) [10]. Also, in two distinct studies conducted by Salari et al [11] and Movaffagh et al [12] it was observed that AUR potentiated the therapeutic effect of IR against cancer cells.…”
Section: Introductionmentioning
confidence: 99%